Picture and Picture Learning Model in Improving Mathematics Learning Outcomes for Students at SDN Wonobodro 01 on Flat Shapes Matter - Purwantyono, Bambang; Nadhiyya, Asa; Anaguna, Nursyam; Manullang, Ketrin R; Marshanawiah, Andi (Journal of Education and Teaching Learning, 2024)
The problem in this research is that the learning outcomes of class II students at SDN Wonobodro 01 are still low in Mathematics on the topic of flat shapes. This is because the learning system provided by the teacher in class is less interesting, causing students to be less enthusiastic about participating in the learning provided. The aim of this research is to determine the increase in mathematics learning outcomes in flat shapes material using the picture and picture learning model for class II students in the first semester of SDN Wonobodro 01. The research method used is classroom action research (CAR) which is carried out in two cycles and every cycle consists of four stages, namely planning, implementation, observation and reflection. The research results showed that the picture and picture model was successful in improving student learning outcomes. This was shown by the results of the percentage of student completion in the pre-cycle of only 19.2% with an average class score of 53.1. Then, in cycle I it increased to 53.8% with an average class score of 64.8 and increased again in cycle II to 92.3% with an average class score of 90.7. Thus, it can be concluded that the use of the picture and picture model in the material for building mathematical data was successful because student learning outcomes increased each cycle.